A simulation based fly optimisation algorithm for swarms of mini autonomous surface vehicles application - Zainal Abidin, Zulkifli (NATL inst science communication-NISCAIR, 2011)
Present paper intends to provide a detailed description of a new bio-inspired Metaheuristic Algorithm. Based on the detailed study of the Drosophila, the flowchart behaviour for the algorithm, code implementation, methodologies and simulation analysis, a novel Fly Optimization Algorithm (FOA) approach is presented. The optimal simulation parameters can be used for the real application. FOA is suitable for applications that need a small number of agents; in the range of 8 to 24 only. The objective of the simulation is to understand the effect of the algorithm parameter on searching pattern strategy, as well as the possibility and the effectiveness of the proposed technique for the Swarm of mini Autonomous Surface Vehicles' (ASVs) application.